2020
DOI: 10.3389/fcvm.2020.00023
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Expression of Mitochondrial Complexes Due to Genetic Variants May Alter Sensitivity to Radiation-Induced Cardiac Dysfunction

Abstract: Radiation therapy is received by over half of all cancer patients. However, radiation doses may be constricted due to normal tissue side effects. In thoracic cancers, including breast and lung cancers, cardiac radiation is a major concern in treatment planning. There are currently no biomarkers of radiation-induced cardiotoxicity. Complex genetic modifiers can contribute to the risk of radiation-induced cardiotoxicities, yet these modifiers are largely unknown and poorly understood. We have previously reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…The simple ganoderma lucidum spore oil system these authors developed targeted the myocardial mitochondria and slowed down the production of roS, thus exhibiting a preventative and therapeutic effect on riHd. additionally, the differences in expression levels of mitochondrial genes caused by genetic variants may lead to differences in sensitivity to ionizing radiation (68). collectively, the aforementioned studies revealed that mitochondrial damage was an important target in riHd, and drugs or drug-loaded materials for the repair of mitochondrial damage can reduce radiation-induced heart injury.…”
Section: Discussionmentioning
confidence: 99%
“…The simple ganoderma lucidum spore oil system these authors developed targeted the myocardial mitochondria and slowed down the production of roS, thus exhibiting a preventative and therapeutic effect on riHd. additionally, the differences in expression levels of mitochondrial genes caused by genetic variants may lead to differences in sensitivity to ionizing radiation (68). collectively, the aforementioned studies revealed that mitochondrial damage was an important target in riHd, and drugs or drug-loaded materials for the repair of mitochondrial damage can reduce radiation-induced heart injury.…”
Section: Discussionmentioning
confidence: 99%
“…A number of different dose and fractionation regimens have been utilized in preclinical studies of RIHD, ranging from large single fractions to more clinically relevant fractionated regimens ( 2 ). We used a fractionated regimen consisting of 8 Gy x 5 fractions, similar to prior studies that have utilized fractionated radiation ( 2 , 19 , 54 ) and which have reported histological changes ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rat hearts treated with a single dose of 2 Gy showed dysregulation of several metabolic proteins isolated from mitochondrial fractions, including proteins involved in the electron transport chain, glycolysis, and lipid metabolism 353 . Interestingly, murine cardiac models of high‐dose radiation have showed downregulation and decreased activity of multiple parts of the electron transport chain, paired with increased activity of pyruvate dehydrogenase E1α 353,354 . These data contrast with observations from irradiated cancer cells, which show a HIF‐1α‐dependent upregulation of mitochondrial complex proteins after comparable doses of X‐rays or gamma irradiation, 184,355 highlighting the differential impact of metabolic reprogramming in cancerous vs normal tissue.…”
Section: Changes To Major Metabolic Pathways Induced By Ionizing Radiationmentioning
confidence: 94%